HUBUNGAN ANTARA NILAI KRITIS DERIVATIF- F^α DENGAN DIMENSI-γ DARI SUATU KURVA - Supriyadi Wibowo (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2012)
Continue function that defined on fractal set is a function which has irregular structure, that can not be an ordinary differentiable on F. In this paper will be explored the correlation between critical point of the derivatif with dimension- of a curve. By using the properties of the derivative , Holder’s continue function in rank of and dimension , has been obtained the correlation between critical value of derivative and the dimension of a curve.